Profesi Engineer dan Strategi Mengatasi Kecemasan Berbahasa Inggris - Suciana Wijirahayu; Rifki Irawan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2018)
One of the reasons why the participants lack speaking skill is they felt anxious when communicating in English in a real situation, especially with foreigners. There are eight participants in this research joined in house training in one of the company in Jakarta-Indonesia The research is mainly qualitative with some descriptive statistics which employed some data collection techniques: two questionnaires, interview, classroom observation, and document analysis. The data were analyzed by ways of reducing, displaying, and interpreting data. Four participants detail expression related to their Foreign Language Anxiety (FLA) will be illustrated and discussed. The results of the study were most of the participants experience a high level of test anxiety, the sources of anxiety coming from people’s view, preparation, procrastination, expectation, negative consequences/ negative thinking, personal problem, time pressure, format usage, students’ age, students’ familiarity with the testing condition, testing situation factors, and not mastering the skill. The participants’ coping strategies are various which are mostly cooperating.